2022
DOI: 10.1111/adb.13229
|View full text |Cite
|
Sign up to set email alerts
|

Classic psychedelics and alcohol use disorders: A systematic review of human and animal studies

Abstract: Classic psychedelics refer to substances such as lysergic acid diethylamide (LSD), psilocybin, ayahuasca, and mescaline, which induce altered states of consciousness by acting mainly on 5-HT 2A receptors. Recently, the interest of psychedelics as pharmacological treatment for psychiatric disorders has increased significantly, including their use on problematic use of alcohol. This systematic review is aimed to analyse the last two decades of studies examining the relationship between classic psychedelics and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 102 publications
(166 reference statements)
0
17
0
Order By: Relevance
“…Serotonergic psychedelics, in general, have been demonstrated to be potential candidates for the treatment of alcohol dependence. A systematic review including 20 human studies and 7 preclinical studies demonstrates overall promising data for psychedelics to effectively treat the symptoms of AUD, and the psilocybin was specifically demonstrated to be the most consistent compound [ 135 ]. The double-blind clinical trial for the treatment of AUD with psilocybin conducted by Bogenschutz et al (NCT identifier number: NCT02061293) demonstrated the most convincing results so far, helping to consider proceeding with a phase 3 clinical trial.…”
Section: Future Directions and Therapeutic Implicationsmentioning
confidence: 99%
“…Serotonergic psychedelics, in general, have been demonstrated to be potential candidates for the treatment of alcohol dependence. A systematic review including 20 human studies and 7 preclinical studies demonstrates overall promising data for psychedelics to effectively treat the symptoms of AUD, and the psilocybin was specifically demonstrated to be the most consistent compound [ 135 ]. The double-blind clinical trial for the treatment of AUD with psilocybin conducted by Bogenschutz et al (NCT identifier number: NCT02061293) demonstrated the most convincing results so far, helping to consider proceeding with a phase 3 clinical trial.…”
Section: Future Directions and Therapeutic Implicationsmentioning
confidence: 99%
“…In indigenous and neoshamanic contexts, ayahuasca, a botanical decoction originating from the Amazonian rainforest, has been routinely used in the treatment of addictions (Talin and Sanabria, 2017). A systematic review by Calleja-Conde et al pointed to significant benefits in both animal and human studies (Calleja-Conde et al, 2022). Reviews by Frecska et al and James et al discussed additional aspects (Frecska et al, 2016;James et al, 2022).…”
Section: Ayahuascamentioning
confidence: 99%
“…Recent years have seen a resurgence in psychedelic research, a development sometimes referred to as the psychedelic renaissance. Since 2016, three systematic reviews have been conducted evaluating the efficacy of psychedelics (i.e., psilocybin, but also other classic serotonergic psychedelics such as LSD were included in these systematic reviews) as a treatment for psychiatric disorders (i.e., SUD, but also other psychiatric disorders such as depression and anxiety were included in these systematic reviews) ( 19 21 ). Although these reviews provide an excellent overview of clinical trials published in the last 25 years, including multiple psychedelics and conditions, they may have missed clinical trials evaluating the efficacy of psychedelics that were conducted before the 1980s ( 19 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2016, three systematic reviews have been conducted evaluating the efficacy of psychedelics (i.e., psilocybin, but also other classic serotonergic psychedelics such as LSD were included in these systematic reviews) as a treatment for psychiatric disorders (i.e., SUD, but also other psychiatric disorders such as depression and anxiety were included in these systematic reviews) ( 19 21 ). Although these reviews provide an excellent overview of clinical trials published in the last 25 years, including multiple psychedelics and conditions, they may have missed clinical trials evaluating the efficacy of psychedelics that were conducted before the 1980s ( 19 21 ). As shown by Fuentes et al ( 6 ), many trials have been conducted assessing the efficacy of LSD in SUD in these early decades, which may have been an important era for psilocybin research as well ( 6 ).…”
Section: Introductionmentioning
confidence: 99%